Assessing the Environmental Impact of Municipal Waste on Energy Incineration Technology for Power Generation Using Life Cycle Assessment Methodology - Yiting Luo; Mingqiang Ye; Yihui Zhou; Rongkui Su; Shunhong Huang; Hangqing Wang; Xiangrong Dai (Toxics)
The life cycle assessment methodology is a comprehensive environmental impact evaluation approach rooted in the “cradle-to-grave” concept. This study takes a municipal solid waste incineration power plant in central China as an example to comprehensively explore the potential ecological and environmental impacts of municipal solid waste incineration power generation through life cycle assessment methods. Burning one ton of waste can recover 7342 joules of thermal energy. Compared with traditional landfill, incineration can reduce greenhouse gas emissions by about 30%, with a potential global warming impact of −0.69 kg of carbon dioxide equivalent. Amongst environmental impacts, land, freshwater, and marine ecosystems possess the greatest potential toxicity, followed by the harmful effects on human health and the influence of ozone-producing photochemical pollution. Lastly, there comes terrestrial acidification, whereas other types of effects can be relatively disregarded in comparison. In the process of waste incineration power generation, the potential impacts of global warming, ionizing radiation, and fossil resource scarcity are less than zero, indicating that this is an environmentally friendly process. In response to the above-mentioned environmental impacts, it is necessary to pay attention to improving incineration efficiency, optimizing leachate treatment, reducing coal use, and controlling acidic gas emissions in the process of urban solid waste incineration power generation. This research offers insights into advancing environmentally sustainable technologies for utilizing waste as an energy resource.